Angular Circle Array Multiple Input Multiple Output Underwater Optical Wireless Communications - Zhuoqi Chen; Yuhe Liu; Xiang Yi; Ruiqin Zhao (Photonics)
This paper constructs a simulation platform for underwater wireless optical single-input single-output (SISO) communication systems and quantitatively evaluates communication performance indicators. To improve channel capacity, we propose an angular circle array MIMO scheme. The path loss, CIR, and channel capacity of the angular circular array MIMO communication system are calculated by using the Monte Carlo method. Results show that the proposed angular circular array MIMO communication system has a higher channel capacity compared to planar circular array MIMO communication systems and SISO communication systems.